Time and time relation in English and in Cebuano - Geonzon, Epifania (Laplap)
The purpose of the study is to investigate the English and Cebuano temporal systems. It describes and contrasts the signals that indicate time and time elation in English and Cebuano. Findings of the study point out areas of difficultuies for Cebuanos in learning to express time, show time relation, and locate action in time in English. The study may help teachers, particularly in Cebuano speaking regions, to point out linguistic basis for sound instructional materials in the teaching of English, especially in the elementary level. The study presents some characteristics of Cebuano language which may be of use to scholars who later will investigate the language for research on linguistics.
Thesis (M.A.T.)--University of the Philippines
Keywords: Cebu dialect -- Tense; English language -- Tense